Phthalates in face masks and their effects on cellular energetics in human bronchial epithelial cells - Lyse Szymanski; Margueritta Al Zallouha; Clémence Bouzar; Edwige Votier; Christelle Monteil; Tiphaine Rogez-Florent (Ecotoxicology and Environmental Safety)
The widespread use of disposable masks has sparked concerns about potential exposure to harmful chemicals, including the already ubiquitous phthalates. It has been demonstrated that there is a causal relationship between the exposure to phthalates and the onset of respiratory diseases. Moreover, there is an increasing body of evidence, which suggests that mitochondria contribute to significant impact to the epithelial function in respiratory diseases. However, the specific effects induced by these compounds at the mitochondrial level in respiratory cells are unknown. The objective of this study was to identify phthalates in disposable face masks and to evaluate their effect on mitochondrial function in human bronchial epithelial cells (BEAS-2B). In order to identify and quantify the phthalates in face masks, an extraction method was developed and a phthalate quantification method using Gas Chromatography-Mass Spectrometry was employed. The analysis of the face masks sample revealed the presence of three major phthalates: di(2-ethylhexyl) phthalate (DEHP), dibutyl phthalate (DBP) and diisobutyl phthalate (DiBP). To evaluate the effects of these phthalates on mitochondrial function, BEAS-2B were exposed to the phthalates individually and in a mixture of the three at concentrations ranging from 0.5 to 10 mg/L for 24 hours. Then extracellular flux analysis (Seahorse analysis), adenosine levels (LC-DAD) and lactate levels (LC-MS) were evaluated. The observed effects at the mitochondrial level varied according to the specific phthalates that were tested. The major dysfunctions were identified following exposure to DEHP, which exerted inhibitory effects on the basal and maximal oxygen consumption rate of BEAS-2B cells, as well as an alteration in oxidative phosphorylation and a reduction in the ATP/ADP ratio. This was accompanied by an increase in both extracellular lactate production and extracellular acidification rate. A shift towards a glycolytic phenotype was noted. Similar, yet more pronounced effects, were observed following exposure to the mixture of the three phthalates, which suggest that DEHP may contribute to the overall effect of the mixture. This study is the first to provide knowledge on the adverse effects of a mixture of phthalates on mitochondrial function in bronchial epithelial cells, demonstrating the capacity of some phthalates to induce a shift toward a glycolytic phenotype. These results highlight the potential risks of inhaled phthalates on mitochondrial function, predisposing to the development of respiratory diseases.